The Production of Nickel-Chromium-Molybdenum Alloy with Open Pore Structure as an Implant and the Investigation of Its Biocompatibility In Vivo - Er, Yusuf; Unsaldi, Emine (Hindawi Ltd, 2013)
A dental crown material, Nickel-Chrome-Molybdenum alloy, is manufactured using precision casting method from a polyurethane foam model in a regular and open-pore form, as a hard tissue implant for orthopedic applications. The samples produced have 10, 20, and 30 (+/-3) pores per inch of pore densities and 0.0008, 0.0017, and 0.0027 g/mm(3) densities, respectively. Samples were implanted in six dogs and observed for a period of two, four, and six months for the histopathological examinations. The dogs were examined radiologically in 15-day intervals and clinically in certain intervals. The implants were taken out with surrounding tissue at the end of these periods. Implants and surrounding tissues were examined histopathologically in terms of biocompatibility. As a result, it is seen that new bone tissue was formed, in pores of the porous implant at the head of the tibia in dogs implanted. Any pathology, inflammation, and reaction in old and new tissues were not observed. It was concluded that a dental alloy (Ni-Cr-Mo alloy) could also be used as a biocompatible hard tissue implant material for orthopedics.
Keywords: Hydroxyapatite; Ti